Peningkatan Kompetensi Keilmuan IOT Melalui Pelatihan Pengontrolan Perangkat IOT dengan Menggunakan Smartphone untuk Siswa SMK dan SMA di Kota Malang - Dahnial Syauqy; Yuita Arum Sari; Putra Pandu Adikara; Muhammad Aminul Akbar; Hurriyatul Fitriyah (Universitas Lancang Kuning, 2020)
The internet has encouraged the emergence of a new paradigm in the use of computing, marked by the emergence of devices that are connected to each other or known as the Internet of Things (IoT). One of the factors that contributed to the rapid emergence of